Revision of the genus Georissus (Coleoptera, Hydrophiloidea, Georissidae) of Japan - Yasuda, Kohei; Yoshitomi, Hiroyuki (European Journal of Taxonomy, 2022)
Japanese species of the genus Georissus are revised. Seven species, including two new, G. (Neogeorissus) takahashii sp. nov. and G. (Ne.) satoi sp. nov. are recognized. Georissus (Neogeorissus) sakaii Satô, 1972 and G. (Ne.) katsuoi Nakane, 1995 are synonymized with G. (Ne.) japonicus Satô, 1972. Based on the type series and additional specimens, three subgenera and seven species are (re)described with SEM micrographs of the external morphology and figures of male and female genitalia. The terminology of some structures of the head and the pronotum are redefined for convenience of taxonomy. A key to the Japanese species is also given.